2009
DOI: 10.1126/science.1180060
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of Carbonic Acid Formation in Aqueous Solution

Abstract: Despite the widespread importance of aqueous bicarbonate chemistry, its conjugate acid, carbonic acid, has remained uncharacterized in solution. Here we report the generation of deuterated carbonic acid in deuterium oxide solution by ultrafast protonation of bicarbonate and its persistence for nanoseconds. We follow the reaction dynamics upon photoexcitation of a photoacid by monitoring infrared-active marker modes with femtosecond time resolution. By fitting a kinetic model to the experimental data, we direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
258
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(297 citation statements)
references
References 36 publications
26
258
0
3
Order By: Relevance
“…Karst carbon sinks were commonly considered as being a reversible process, nevertheless, work by Adamczyk et al [36] showed that aquatic CO 2 is much more stable than our understanding of karst carbon sink processes. This finding provides basic support for determining the stability of HCO 3 -in surface water, which is circulated from underground karst water, and for estimating net carbon sinks.…”
Section: Resultsmentioning
confidence: 99%
“…Karst carbon sinks were commonly considered as being a reversible process, nevertheless, work by Adamczyk et al [36] showed that aquatic CO 2 is much more stable than our understanding of karst carbon sink processes. This finding provides basic support for determining the stability of HCO 3 -in surface water, which is circulated from underground karst water, and for estimating net carbon sinks.…”
Section: Resultsmentioning
confidence: 99%
“…At low pH, the amount of H 2 CO 3 relative to CO 2 (aq) is extremely small, less than 0.2% (Falcke and Eberle, 1990;Tossell, 2006;Adamczyk et al, 2009;England et al, 2011;Soli and Byrne, 2002 In order to calculate a composite D 63 for the DIC pool at low pH, we make the following assumptions. Since the hydration of CO 2 (aq) occurs at a much slower rate than the deprotonization of H 2 CO 3 to HCO À 3 (i.e., stripping off a proton occurs much more rapidly than acquiring an extra O to form a carbonate ion) (Adamczyk et al, 2009), we assume that any carbonate mineral precipitating rapidly from a DIC pool at low pH will form from the instantaneous H 2 CO 3 and HCO À 3 components of the DIC pool and not directly from CO 2 (aq). For the purpose of the current first order calculations, we ignore any subsequent conversion of CO 2 (aq) to H 2 CO 3 or HCO À 3 .…”
Section: Discussionmentioning
confidence: 99%
“…We now demonstrate the power of this interferometric detection for stimulated Raman signals commonly used to probe molecular vibrations. Applications include probing time-resolved photophysical and photochemical processes (Adamczyk et al, 2009;Kukura et al, 2007;Kuramochi et al, 2012;Schreier et al, 2007), chemically specific biomedical imaging (Cheng et al, 2002), remote sensing (Arora et al, 2012;Pestov et al, 2008). Considerable effort has been devoted to increasing the sensitivity and eliminating off-resonant background, thus improving the signal-to-noise ratio and enabling the detection of small samples and even single molecules.…”
Section: Coincidence Detection Of Femtosecond Stimulated Raman Signalsmentioning
confidence: 99%